Analysis of Rhodamine B in Lip Creams from Marketplace - Dea Christina, Odilia; Pitarisa, Agustina Putri (Journal of Food and Pharmaceutical Sciences, 2024)
Lip cream is a cosmetic product with a creamy texture that provides long-lasting color for the lips. One of the cosmetic colorants often misused as a lip colorant is Rhodamine B, which is supposed to be used for textile coloring. Rhodamine B may cause irritation, is carcinogenic, and can even cause liver damage in high concentrations. This study aims to determine whether lip creams sold in marketplaces contain Rhodamine B and measure the concentration of Rhodamine B in these products. Qualitative analysis of the Rhodamine B content in lip cream was carried out using the thin layer chromatography (TLC) method with the stationary phase silica gel GF254 and the mobile phase n-butanol: ethyl acetate: 25% ammonia with a ratio of 10:4:5. Of the 5 samples that were qualitatively analyzed using TLC, 3 samples were positive for containing rhodamine B, samples number 1, 2, and 3. Quantitative analysis was conducted to determine Rhodamine B concentrate using the spectrophotometry UV-Vis method with a maximum wavelength of 546 nm. The results of assay determination showed that the average concentration containing rhodamine B was 0.044% in sample number 1, 0.060% in sample number 2, and 0.052% in sample number 3.